Occult Spinal Dysraphism in Obstetrics: A Case Report of Caesarean Section with Subarachnoid Anaesthesia after Remifentanil Intravenous Analgesia for Labour - A. Valente; L. Frassanito; L. Natale; G. Draisci (Case Reports in Obstetrics and Gynecology)
Neuraxial techniques of anaesthesia and analgesia are the current choice in obstetrics for efficacy and general low risk of major complications. Concern exists about neuraxial anaesthesia in patients with occult neural tube defects, regarding both labour analgesia and anaesthesia for Caesarean section. Recently, remifentanil infusion has been proposed as an analgesic technique alternative to lumbar epidural, especially when epidural analgesia appears to be contraindicated. Here, we discuss the case of a pregnant woman attending at our institution with occult, symptomatic spinal dysraphism who requested labour analgesia. She was selected for remifentanil intravenous infusion for labour pain and then underwent urgent operative delivery with spinal anaesthesia with no complications.